SOCIOECONOMIC DISADVANTAGE IN EARLY LIFE PREDICTS POOR PHYSICAL PERFORMANCE IN LATE LIFE AMONG OLDER JAPANESE. (11th November 2018) - Murayama, H; Sugiyama, M; Inagaki, H; Ura, C; Miyamae, F; Edahiro, A; Okamura, T; Awata, S
Abstract: Background: It is important to maintain physical function in old age to prevent disability. Previous studies explored factors related to physical decline, but most have focused on these processes during mid- and late-life. Recently, life course strategies have been proposed for disability prevention from early life stage. However, there is sparse evidence regarding whether childhood socioeconomic disadvantages are related to physical function in old age. This study examined the association between childhood socioeconomic status (SES) and physical performance among older Japanese. Methods: A cross-sectional questionnaire survey was conducted in 2015. The participants were all residents aged 65+, living in Adachi ward in the Tokyo metropolitan area (n=132, 005). To assess physical performance, we used the Motor Fitness Scale (14-item; range 0–14) which includes three components of mobility, strength, and balance. The reliability and validity were confirmed. Childhood SES was determined with a single question asking respondents to categorize into five (high, middle-high, middle, middle-low, and low). Covariates included socio-demographics, health behaviors, and health conditions. Results: The analysis included 75, 358 questionnaires. Mean age was 73.8 years (SD=6.0), and 45.0% were men. An ordinal logistic regression analysis showed a dose-response relationship between lower childhood SES and poorer physical performance after adjusting for covariates. There was an effect modification of gender: the association was stronger in female than that in male. Conclusions: Lower SES in early life was associated with poorer physical performance in late life. This suggests a long-term influence of childhood socioeconomic disadvantage on physical function later in life.